Епоксидування α-пінену та Δ³-карену пероксикислотами в різних розчинниках - Дутка, В.; Самсонова, І.; Дутка, Ю.; Колобова, В. (Праці наукового товариства ім. Шевченка, 2011)
Вивчено реакцію епоксидування a-пінену та Δ³-карену пероксидекановою кислотою в різних органічних розчинниках. Показано, що реакційне середовище впливає на швидкість процесу. Знайдено ефективні енергії активації реакції епоксидування a- пінену і Δ³-карену пероксидекановою кислотою в різних середовищах. The reaction of α-pinene and Δ³-karene epoxidation by peroxydecanoic acid (PDA) in different solvents was studied. The effective pseudomonomolecular constants of α-pinene and Δ³-karene epoxidation were found. Energies of activation of α-pinene epoxidation with PDA have limits 24,0 – 64,2 kJ/mol and for Δ³-karene epoxidation energies of activation are lower and for investigated solvents lie in the limits 20,4 – 57,7 kJ/mol. Δ³-karene epoxidation passes easier, than α-pinene. In both cases in the investigated series of solvents linear relationship between parameters of transfer state ΔH# and ΔS # is observed. The indemnificate effect presence witnesseths about the difficult solvent influence on the studied reactions. The optimal geometric structure and heats of formation of investigated bicycled terpenoids and their epoxycompounds with quantum-chemical half empirical method AM1 was calculated. The high reaction stereospecifics were confirmed. The attack of peroxyacid molecule on the double bond in terpenoide molecule on the double bond in terpenoide molecule passes from α-area. Изучено реакцию эпоксидирования a-пинена и Δ³-карена пероксидекановой кислотой (ПДК) в различных органических растворителях. Показано, что реакционная среда оказывает существенное влияние на скорость процесса. Определены эффективные энергии активации реакции окисления a-пинена и Δ³-карена ПДК в различных органических средах.